Equal Treatment in Healthcare Irrespective of Racial or Ethnic Origin in the EU and Slovenia - Ramšak, Mojca (Medicine, Law & Society, 2020)
The systematic review and analysis of legal acts aims to answer the question if people from diverse ethnic and racial backgrounds in EU Member States have equal access to healthcare and what is the degree of implementation of equal tratment in Slovenia. The overall reason of this analysis is to find the potential gaps in the access to health system for people from diverse ethnic and racial backgrounds and to decrease disparities between dominant and minority groups. Both, EU and Slovenia, prohibit discrimination on the grounds of racial or ethnic origin and have strong measures to combat discrimination on these grounds. Regardless the legislation and special protection, inequalities experienced in the most vulnerable and marginalised groups, such as Roma, migrant workers, asylum seekers, still remain an ongoing challenge.